Feasibility Study for Investment in VSPP Solar Power Plant in Thailand Using GIS and Financial - Ratanasuwan, Rachata; Paoprasert, Naraphorn; Yousuk, Ramidayu (UPN Veteran Jatim, 2025)
The study aims to evaluate the financial feasibility and land suitability for investment in VSPP solar plant in Thailand using Geographic Information System (GIS) and financial modeling techniques. The study analyze key parameters, including photovoltaic power output (PVOUT), land price, and distance from existing infrastructure. The methodology comprises GIS-based spatial analysis and financial performance assessment using indicators consisting of the Net Present Value (NPV), the Project Internal Rate of Return (PIRR), the Equity Internal Rate of Return (EIRR), and the simple payback period (SPB) to identify area and location for investment in VSPP solar power plant. The study areas were categorized into three groups based on the values of PVOUT - the 10% lowest PVOUT (Group 1), middle range PVOUT (45%-55%) (Group 2), and 10% highest PVOUT (Group 3). The results indicated that locations with the highest 10% PVOUT (Group 3) demonstrated the best financial performance, with an NPV of approximately 15 million THB, PIRR of 9.75%, EIRR of 11.50%, and a SPB of 9.25 years. Conversely, locations with the lowest 10% PVOUT (Group 1) were financially infeasible.